Leadership, organizational commitment and service quality in private higher educational institutions: a case study of a private higher educational institution in Cyberjaya / Siti Maisara Unaizah Mustafa - Mustafa, Siti Maisara Unaizah (2014)
The study on leadership in higher educational institutions has been mentioned as problematic due to the internal conflicts occurred among staffs, the indistinguishable goals and other propertied of the institutions. The success of an organization is based on the capability of the academic leaders as well as the top management in the institutions to solve problems and as well as to develop strategic planning with the participations of all contributors. The main objective of this study was to examine the impact of the leadership behavior and organizational commitment perceived by staff towards the service quality of a private higher educational institution in Cyberjaya. Finding showed that the perceived leadership behaviour and organizational commitment by staff have moderate impact towards the service quality of a private higher educational institution in Cyberjaya. The top management should utilize different leadership behaviours depending on the surroundings. The top management should create a positive working environment within the organization to enhance staffs’ organizational commitment. This study contributes to the understanding on the influence of perceived leadership behaviour and organizational commitment of staff towards the service quality of private higher educational institutions.